Anticoagulation for venous thromboembolism - Pishko, Allyson (Henry Stewart Talks, 2023)
Indications for anticoagulation, Venous thromboembolism (VTE): incidence, treatment, and duration, ‘Natural’ anticoagulants, Heparin, Low molecular weight heparin, Direct thrombin inhibitors, Warfarin, Direct oral anticoagulants, Provoked VTE, Unprovoked VTE